2013
DOI: 10.1371/journal.pone.0077674
|View full text |Cite
|
Sign up to set email alerts
|

Local NMDA Receptor Blockade Attenuates Chronic Tinnitus and Associated Brain Activity in an Animal Model

Abstract: Chronic tinnitus has no broadly effective treatment. Identification of specific markers for tinnitus should facilitate the development of effective therapeutics. Recently it was shown that glutamatergic blockade in the cerebellar paraflocculus, using an antagonist cocktail was successful in reducing chronic tinnitus. The present experiment examined the effect of selective N-methyl d-aspartate (NMDA) receptor blockade on tinnitus and associated spontaneous brain activity in a rat model. The NMDA antagonist, D(−… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
38
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(40 citation statements)
references
References 40 publications
2
38
0
Order By: Relevance
“…Functional imaging studies have also suggested that the PFL is involved in gating or modulating tinnitus (Brozoski et al, 2007; Chen et al, 2015). This interpretation was supported by behavioral studies showing that tinnitus was suppressed or enhanced by inactivating or activating the PFL (Bauer et al, 2013; Brozoski et al, 2007; Brozoski et al, 2013). Noise-induced spontaneous hyperactivity in the IC, considered a neural correlate of tinnitus, is enhanced by removal of the PFL whereas PFL removal had no effect on spontaneous activity in normal animals (Vogler et al, 2016).…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…Functional imaging studies have also suggested that the PFL is involved in gating or modulating tinnitus (Brozoski et al, 2007; Chen et al, 2015). This interpretation was supported by behavioral studies showing that tinnitus was suppressed or enhanced by inactivating or activating the PFL (Bauer et al, 2013; Brozoski et al, 2007; Brozoski et al, 2013). Noise-induced spontaneous hyperactivity in the IC, considered a neural correlate of tinnitus, is enhanced by removal of the PFL whereas PFL removal had no effect on spontaneous activity in normal animals (Vogler et al, 2016).…”
Section: Discussionmentioning
confidence: 77%
“…In the case of chronic noise-induced tinnitus, manganese enhanced magnetic resonance imaging (MEMRI) revealed enhanced spontaneous activity in the PFL. Moreover, behavioral evidence of chronic noise-induced tinnitus was abolished by lesioning or inactivating the PFL (Bauer et al, 2013; Brozoski et al, 2007; Brozoski et al, 2013). Collectively, the imaging and behavioral results suggest that the PFL is involved in gating or modulating tinnitus and hyperacusis.…”
Section: Introductionmentioning
confidence: 99%
“…In the present study we examined whether non-competitive NMDA inhibition with round window applied AM-101 may be beneficial in counteracting the trauma-related deterioration of the IHC synapse and the maladaptive auditory patterns in the ascending auditory pathway during tinnitus [4,49]. It was already shown that the competitive NMDA receptor antagonist D-AP5 (D(-)-2-amino-5-phosphonopentanoic acid), when infused into non-auditory regions (paraflocculus) of rats months following noise exposure had a long-term relieving effect for tinnitus perception [50]. In case of synaptopathic tinnitus, the therapeutic time window of NMDA receptor inhibition not exactly known.…”
Section: Discussionmentioning
confidence: 99%
“…Ifenprodil is a specific NMDA receptor antagonist that blocks NR2B receptor-mediated calcium currents and associated signal transduction pathways [Brozoski et al, 2013]. Ifenprodil (I2892, Sigma, MO, USA) was added to coculture medium at a concentration of 10 μM for 24 h prior to radiation exposure [Anastasio et al, 2009].…”
Section: Cell Culturementioning
confidence: 99%